Analisis Pemanfaatan Media Digital dalam Mendukung Pembelajaran Deep Learning pada PPKn di Sekolah Dasar - Aufa Nabila; Jeky Kurniawan; Adrias Adrias (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
Pancasila and Civic Education (PPKn) plays a vital role in shaping the nation’s character; however, in practice, PPKn instruction in elementary schools is often dominated by conventional methods, resulting in a monotonous learning process. Therefore, an innovative approach is needed—specifically, a deep learning approach that emphasizes deep understanding and critical thinking skills. This study aims to analyze the use of digital media in supporting the implementation of the deep learning approach in PPKn lessons in elementary schools. This study uses a qualitative approach with a systematic literature review method. Data were collected through the Publish or Perish and Google Scholar databases using relevant keywords. Articles were selected based on inclusion and exclusion criteria through the stages of identification, screening, eligibility, and inclusion, resulting in ten articles for analysis. The results of the study indicate that the use of digital media has a positive impact on the application of deep learning in Civic Education (PPKn) instruction, particularly in enhancing students’ conceptual understanding, critical thinking skills, and engagement. Thus, digital media is effective as a supportive tool for optimizing more meaningful and enjoyable Civic Education (PPKn) learning.